2021
DOI: 10.1093/jeea/jvaa060
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning in Higher Education: Evidence from a Randomized Experiment

Abstract: Using a randomized experiment in a public Swiss university, we study the impact of online live streaming of lectures on student achievement and attendance. We find that (i) attending lectures via live streaming lowers achievement for low-ability students and increases achievement for high-ability ones; (ii) students use the live streaming technology only occasionally, apparently when random events make attending in class too costly, and (iii) offering live streaming reduces in-class attendance only mildly. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…However, especially at the beginning of the term, online teaching was less effective, likely because both students and lecturers had to get used to the new teaching methods and to the overall situation of the pandemic. Cacault et al (2019) find that high-skilled students benefit more from online teaching compared to low-skilled students; our quantile regressions show the opposite in times of the pandemic. Likely that is because, in our data, student attendance is positively correlated with performance.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, especially at the beginning of the term, online teaching was less effective, likely because both students and lecturers had to get used to the new teaching methods and to the overall situation of the pandemic. Cacault et al (2019) find that high-skilled students benefit more from online teaching compared to low-skilled students; our quantile regressions show the opposite in times of the pandemic. Likely that is because, in our data, student attendance is positively correlated with performance.…”
Section: Discussionmentioning
confidence: 57%
“…According to Bowen et al (2014), hybrid systems have the potential to achieve at least equivalent outcomes. Another recent study is conducted by Cacault et al (2019). They find that online livestreaming of classes increases the performance of high-achieving students, while the opposite is true for low achievers.…”
Section: Introductionmentioning
confidence: 98%
“…Since the outbreak of COVID-19, researchers and policymakers have focused their attention on its short-term aspects (Barro et al, 2020;Binder, 2020;Fetzer et al, 2020;Fornaro and Wolf, 2020), although some long-term mechanisms have been indicated, like those operating on human capital (Cacault et al, 2021) and women's fertility (Silverio-Murillo et al, 2021). Public debt levels will increase significantly (Chakrabarty and Roy, 2021), and the zero lower bound constraint on interest rates will be still more biting (Costa Junior et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The assessing system for the part-time students is equivalent to the full-time students, as described in the section The Master's Programme in Visual and Performing Arts at OsloMet. Cacault et al (2019) performed a randomised experiment in a Swiss public university on the impact of distance learning technology via online live streaming of lectures on student performance and reported that: I. students use the live streaming technology only punctually, apparently when random events make attending in class too costly; II.…”
Section: Discussion In Relation To Relevant Literaturementioning
confidence: 99%